The changing perception of pediatric dental practice post-COVID: The new normal - Shraddha Saikia; Shivani Mathur (Wolters Kluwer Medknow Publications, 2022)
The outbreak of coronavirus has wreaked havoc as it has become a global emergency. It has affected the entire world population as well as the economy due to its uncontrolled spread. Amidst all sectors which are heavily affected, the health-care unit is exposed to the highest risk as they are on the frontline of combating the novel virus. This risk is far more elevated for dentists due to their work being confined to the oral cavity through which maximum transmission has occurred. Pediatric dentists faced a formidable challenge as the children are mostly asymptomatic carriers of the novel virus. Recently, various protective guidelines have been recommended by various health-care associations such as World Health Organization, American Dental Association, and Center for Disease Control and Prevention around the globe. However, due to the boisterous expansion of this virus, the various spheres such as markets, government and private offices, transport, and dental practice have now started to function with proper guidelines and safety measures. Thus, the most afflicted dental practice is also back to serve the masses for comprehensive oral health care. Along with emergency procedures undertaken ensuring strict regulations of protection, dentistry is now emerging to service with the new normal post-COVID era to take up all essential procedures. Thereupon, this article will shed some light on the post-COVID new normal era of pediatric dentistry.